The impact of organizational culture on the performance of employees from the point of view of middle management - Al-Majali, Bashar Abdul Majeed (Arab Journal for Sciences and Research Publishing, 2016)
The organizational culture is one of the most important constituents in the organization and its adaptation with the surrounding environment, And this study aims to explain the effect of the organizational culture on the performance of NITC’s staff Since a sample of 43 employees with different positions were chosen (middle management) ,This study confirmed the descriptive and analytical method by designing questionnaires and spreading the same on the chosen sample, this analyze the results by SPSS. This study concluded to many results the most important one is that there is a relationship between the organizational culture and the NITC staff’s performance, and the most effective dimension on the staff performance was the team work then the Understand the concept of organizational culture then the perception, then time respect, and last but not least the post decision making, and there is no relationship between the organizational culture and the demographic elements. Study recommends designing a mechanism to involve the staff in decision making and to activate the mechanism of full utilization of time to get to a higher productivity.